THE DEVELOPMENT OF THE EXPLOSIVE LEG STRENGTH OF THE FEMALE VOLLEYBALL TEAM DURING THE COMPETITION SEASON - Jaroslav Popelka; Ratko Pavlović (Sport Scientific And Practical Aspects, 2025)
The author of the thesis addresses the development of the explosive leg strength of the female volleyball team during the competition season. The main method of collecting data was by means of various testing and the evaluation was carried out by means of logical, mathematical and statistical methods as well as a subject analysis. The coaching results refer to the advisability of implementing work-out exercises during competitions to enhance the performance of the players’ explosive leg strength attained during the preliminary period. The results of this study have statistically confirmed the positive effect of explosive leg strength (p < 0.05). The author has concluded his thesis with several recommendations for practice.